A human skin equivalent burn model to study the effect of a nanocrystalline silver dressing on wound healing. Issue 2 (March 2021) - Iljas, J.D.; Röhl, J.; McGovern, J.A.; Moromizato, K.H.; Parker, T.J.; Cuttle, L.
Highlights: A new in vitro, multi-cellular, human skin equivalent burn model was developed. The model displays re-growth after burn injury, but burned native explant does not. Silver dressing delayed or reduced skin re-growth after burn injury. Silver particles were detected in the dermis using histology and mass-spectrometry. Abstract: In this study, a deep burn wound model was established using a 3D human skin equivalent (HSE) model and this was compared to native skin. HSEs were constructed from dermis derived from abdominoplasty/breast surgery and this dermal template was seeded with primary keratinocytes and fibroblasts. The HSE model was structurally similar to native skin with a stratified and differentiated epidermis. A contact burn (60 °C, 80 °C, 90 °C) was applied with a modified soldering iron and wounds were observed at day 1 and 7 after burn. The HSEs demonstrated re-growth with keratinocyte proliferation and formation of a neo-epidermis after burn injury, whereas the ex vivo native skin did not. To assess the suitability of the 3D HSE model for penetration and toxicity studies, a nanocrystalline silver dressing was applied to the model for 7 days, with and without burn injury. The effect of silver on skin re-growth and its penetration and subcellular localization was assessed in HSEs histologically and with laser ablation-inductively coupled plasma mass spectrometry (LA-ICPMS). The silver treatment delayed or reduced skin re-growth, and silver particles were detected on the top of the epidermis, and within the papillary dermis. This novel in vitro 3D multicellular deep burn wound model is effective for studying the pathology and treatment of burn wound injury and is suitable for penetration and toxicity studies of wound healing treatments.